POLA HUBUNGAN PRODUKSI INDUSTRI RUMAH TANGGA BATIK TULIS DENGAN PABRIKAN BATIK CAP -TULIS DAN MANUFAKTUR BATIK PRINTING -TULIS - Mahendra Wijaya (Universitas Nasional, 2010)
Up to now, the history of batik industry in Surakarta is still fascinating to research. By using a method describing economic social process on both sides and simultaneously make a sub contract context dynamics between big modern industry with traditional household industry, so that, the variety of batik production system tends to use domination pattern and functional pattern.